Factores protectores y de riesgo en las complicaciones cardiovasculares de los diabéticos de 40 a 79 años. Loja. 2016. - Cano Saénz, Elizabeth del Pilar (2017)
The Cardiovascular complications in diabetics are the leading causes of morbidity and mortality worldwide, becoming a serious health problem, of multifactorial component and also multidisciplinary action. The present research shows the results of a survey conducted to evaluate how the family functionality and the clinical and socioeconomic factors influences the presence of cardiovascular complications in diabetic patients aged between 40 to 79 years in Loja, Case-control studies were performed on 500 individuals with a diagnosis of diabetes mellitus 2 (DM2), where the cases are of those with cardiovascular complications and the controls are for those who do not present such complication. The Family Functionality Assessment Questionnaire (FFSIL) was applied; and The Morisky-Greene test was used to determine the therapeutic adherence; For the socioeconomic aspects, the INEC survey was applied and for the clinical characteristics, and my own surveys were used as laboratory tests. 362 of the participants did not present cardiovascular complications and 138 presented the complication, with an average age of 61 years, predominantly on females, with onset of the disease between 40 and 64 years, less than half of families show good metabolic control, only elementary education prevail in the group, with a typical average socioeconomic level, stress is present in moderate dysfunctional families. Concluding: the poor control of blood pressure, the evolution time greater than 10 years, the presence of comorbidities, dyslipidemia with predominance of HDL and lack of adherence to the treatment of diabetes are associated with an increased risk of presenting CVD in diabetic subjects. However, those with family dysfunction, poor family support and states of depression, anxiety and stress had positive associations with an increased risk of CVD without achieving statistical significance Keywords: family dysfunction, complications of diabetes, diabetic cardiomyopathies